2016
DOI: 10.4236/jcdsa.2016.65023
|View full text |Cite
|
Sign up to set email alerts
|

FT-IR Microspectroscopic Imaging of Cross-Sectioned Human Hair during a Bleaching Process

Abstract: We investigated bleached human hair by FT-IR microspectroscopy and chemical imaging. The cross sectioned hair is approximately 90 μm in diameter, showed cuticle and cortex in chemical imaging. Differential amide I/II absorbance ratio and broadening amide I band between in the cortex and cuticle were confirmed in FT-IR microspectroscopy and chemical imaging. The cystine monoxide band from the products of disulfide oxidation of the amino acid cystine is associated with hair damaging during bleaching process. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 19 publications
1
20
0
1
Order By: Relevance
“…Fourier transform infrared spectroscopy analysis permits the observation of oxidative damage. An increase in the amide I and amide II bands is observed in bleached hair, showing the content of cysteic acid in the hair . The present results showed that the hair treated with formaldehyde and glyoxylic acid did not present oxidative damage since there was no change in the cysteic acid content.…”
Section: Discussionsupporting
confidence: 55%
“…Fourier transform infrared spectroscopy analysis permits the observation of oxidative damage. An increase in the amide I and amide II bands is observed in bleached hair, showing the content of cysteic acid in the hair . The present results showed that the hair treated with formaldehyde and glyoxylic acid did not present oxidative damage since there was no change in the cysteic acid content.…”
Section: Discussionsupporting
confidence: 55%
“…The FTIR microspectroscopy was used to investigate the effects of hair bleaching [43]. Black virgin hair was bleached for 30–120 min in the presence of hydrogen peroxide (6%).…”
Section: Spectroscopic Techniquesmentioning
confidence: 99%
“…The quantity of the by‐products increased with increasing bleaching time. Physical appearance analysis revealed square‐shaped cross‐sections of the hair samples [43].…”
Section: Spectroscopic Techniquesmentioning
confidence: 99%
“…The damage on hair after chemical treatment can be assessed using an attenuated total reflectance-Fourier transform infrared spectrophotometer (ATR-FTIR) to detect the presence of characteristic cysteic acid peak at 1040-4 cm −1 [14]. Hair damage assessment is possible because the bonds in hair keratin and their derivatives absorb in the infrared region and produce characteristic vibrational frequencies [14,16,17]. ATR-FTIR is gaining popularity because it is non-destructive to the sample and requires less or no sample preparation [18,19].…”
Section: Introductionmentioning
confidence: 99%